Evaluation on the performance of aged asphalt binder and mixture under various aging methods - Idham, Mohd. Khairul (Penerbit UTM Press, 2015)
Hot mix asphalt (HMA) pavement encounter short and long term aging throughout the service life. Laboratory aging is the method used to simulate field aging process of HMA pavement. This study was undertaken to determine the long term effect of different binder and mixture laboratory aging methods on HMA (binder aging and mixture aging). Three types of HMA mixtures were prepared for this study namely Asphaltic Concrete with 10 mm nominal maximum aggregate size (AC 10), Asphaltic Concrete 14 mm (AC 14) and Asphaltic Concrete 28 mm (AC 28). These specimens were conditioned with nine different methods and durations. Resilient modulus test was carried out at 40°C as an initial indicator of the specimen performance. Permanent deformation of the same specimens was then evaluated by dynamic creep test. Generally, the aged asphalt binder specimens have higher resilient and stiffness modulus compared to aged asphalt mixture specimens. In addition, aged binder specimens have a lower permanent strain which indicates higher resistance to permanent deformation. This study also found that high resilient and stiffness modulus of specimens is attributed by different in heating frequency, temperature, air exposure and binder content of the mixtures